Translation Method in Song Lyric “Cintanya Aku” From Indonesian to English - Sihite, Rani Amelia; Marbun, Waldi; Hutabarat, Sabrina Wandani; Saragih, Frans Ananda (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
This study analyzes the translation methods in the lyrics of the song